BOOM AND BUST: ANCIENT AND RECENT DIVERSIFICATION IN BICHIRS (POLYPTERIDAE: ACTINOPTERYGII), A RELICTUAL LINEAGE OF RAY‐FINNED FISHES. (2nd January 2014) - Near, Thomas J.; Dornburg, Alex; Tokita, Masayoshi; Suzuki, Dai; Brandley, Matthew C.; Friedman, Matt
<x xml:space="preserve">Abstract</x> Understanding the history that underlies patterns of species richness across the Tree of Life requires an investigation of the mechanisms that not only generate young species‐rich clades, but also those that maintain species‐poor lineages over long stretches of evolutionary time. However, diversification dynamics that underlie ancient species‐poor lineages are often hidden due to a lack of fossil evidence. Using information from the fossil record and time calibrated molecular phylogenies, we investigate the history of lineage diversification in Polypteridae, which is the sister lineage of all other ray‐finned fishes (Actinopterygii). Despite originating at least 390 million years (Myr) ago, molecular timetrees support a Neogene origin for the living polypterid species. Our analyses demonstrate polypterids are exceptionally species depauperate with a stem lineage duration that exceeds 380 million years (Ma) and is significantly longer than the stem lineage durations observed in other ray‐finned fish lineages. Analyses of the fossil record show an early Late Cretaceous (100.5–83.6 Ma) peak in polypterid genus richness, followed by 60 Ma of low richness. The Neogene species radiation and evidence for high‐diversity intervals in the geological past suggest a "boom and bust" pattern of diversification that contrasts with common perceptions of relative evolutionary stasis in so‐called "living fossils."